Children’s pre-academic school readiness and home learning activities: a moderated-mediation analysis of home visiting - Avelar, Daniela; Hull, Darrell; Middlemiss, Wendy (Frontiers in Psychology, 2023)
The current study explores the relation between parent involvement and children's school readiness for 568 families enrolled in the Home Instruction of Preschool Youngsters (HIPPY) program in Texas. Parent involvement in children's learning is a focus of the HIPPY curriculum. In this analysis, conditional process models were run to examine the relations between children's school readiness and engagement in home learning activities, parents' education level, program language (English or Spanish), both before and after completing a year of the program. At pretest but not posttest, program language moderated the direct relation between parents' education level and children's school readiness and parents with high levels of education were more likely to engage their children in educational activities. Engagement in home learning activities was associated with school readiness regardless of parents' education level and language. These findings provide a better understanding of the variables associated with school readiness for HIPPY families, indicating the importance of home learning activities-a variable that may be more amenable to change within intervention programs. Thus, focusing on home learning activities may contribute to decreasing discrepancies in children's preparedness for school entry that are generally identified across language and parent education. Findings may have practical implications for other home visitor programs working with similar populations.